Emotional context, maternal behavior and emotion regulation - Roque, Lisa (2012)
This study investigated the importance of emotion-eliciting context (positive and negative) and mother’s behaviors (constrained and involved) on toddlers’ emotion regulation behavioral strategies, emotional expressiveness and intensity, during three episodes eliciting fear, frustration/anger and positive affect. Fifty-five children between 18 and 26 months of age and their mothers participated in the study. Toddlers’ regulatory strategies varied as function of emotion-eliciting context (children exhibited behavioral strategies more frequently during positive affect and frustration/anger episodes and less frequently during fear episodes) and maternal involvement. Toddlers’ expression of emotion varied as function of emotion-eliciting context (children exhibited more emotional expressions, both negative and positive during fear and frustration/anger episodes compared to positive affect episodes). Toddlers’ expression of emotion was not strongly related to maternal involvement, however, the intensity of emotional expression was related to the interaction of context and maternal involvement.